Trip and parking generation study of emerging food parks - Salas, Allan David G.; Escorido, Mark Angelo M.
Trip and parking generation study are done to determine the traffic characteristics of a development or land use type to the transportation and traffic system. The output for such study includes trip rates, modal split, and parking demand. Food parks are becoming more popular these days. They are usually found near schools and residential areas. This study aims to determine the trip rate for food parks, modal split of trips generated by food park, its parking demand, and the independent variable that best describes trip rate and parking demand. Results of analysis show that the gross floor area (GFA) is the best independent variable to use in generating trip rate and estimating trip ends as compared with other characteristics such as seating capacity and number of stalls. The results from the modal split survey showed that the environment in which the food parks are located affects the preferred mode of transportation of the customers. Like modal split, parking demand generation rate is also dependent on the location of the food parks. None of the independent variables used in the Parking Generation Study passed the criteria set by ITE. Thus, it is deemed that the classification of the site location must be considered to obtain meaningful results.